A meta‐analysis to determine the oncological implications of conversion in laparoscopic colorectal cancer surgery. (June 2015) - Clancy, C.; O'Leary, D. P.; Burke, J. P.; Redmond, H. P.; Coffey, J. C.; Kerin, M. J.; Myers, E.
Abstract Aim Laparoscopic colon and rectal cancer surgery is oncologically equivalent to open resection, but the impact of conversion is undetermined. The aim of this study was to assess the oncological outcome and predictive factors associated with conversion. Method A comprehensive search for published studies examining the associated factors and outcome of conversion from laparoscopic to open colorectal cancer resection was performed adhering to PRISMA (Preferred Reporting Items in Systematic Reviews and Meta‐analyses) guidelines. Only randomized control trials and prospective studies were included. Each study was reviewed and the data extracted. Random effects methods were used to combine data. Results Fifteen studies, including 5293 patients, met the inclusion criteria. Of these 4391 patients had a completed laparoscopic resection and 902 were converted to an open resection. The average conversion rate of the studies was 17.9 ± 10.1%. Meta‐analysis showed completed laparoscopic surgery favoured lower 30‐day mortality (OR 0.134, 95% CI 0.047–0.385, P < 0.0001), lower long‐term disease recurrence (OR 0.634, 95% CI 0.421–0.701, P < 0.023) and lower overall mortality (OR 0.512, 95% CI 0.417–0.629, P < 0.0001). Factors negatively associated with completion of laparoscopic surgery were male gender (P = 0.011), rectal tumour (P = 0.017), T3/T4 tumour (P = 0.009) and node‐positive disease (P = 0.009). Completed laparoscopic surgery was also associated with a lower body mass index (BMI; mean difference −0.93 kg/m2, P = 0.004). Conclusion The results suggest that conversion from laparoscopic to open colorectal cancer resection is influenced by patient and tumour characteristics and is associated with an adverse perioperative outcome. Although confounding factors such as advanced tumour stage and elevated BMI are present, unsuccessful laparoscopic surgery appears to be associated with an adverse long‐term oncological outcome.